High-content phosphogypsum-cement stabilized macadam mixture and preparation method thereof

By using high-addition phosphogypsum-cement stabilizes the gravel mixture in pavement materials, phosphogypsum activity is stimulated and stabilized, the problems of low doping ratio, poor stability and water stability of phosphogypsum in pavement materials are solved, and the effect of efficient utilization of phosphogypsum and reducing road construction costs is achieved.

CN119638356APending Publication Date: 2025-03-18CHINA METALLURGICAL CONSTR ENG GRP +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411832422.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

When used in pavement materials, phosphogypsum has problems such as low doping ratio, poor stability and water stability.

Method used

High-addition phosphogypsum-cement is used to stabilize the gravel mixture. By stimulating the activity of the original phosphogypsum with cement and curing agent, and stabilizing the gravel with water, the amount of phosphogypsum is increased.

Benefits of technology

The method of high-addition phosphogypsum is achieved, and high-addition phosphogypsum-cement is prepared instead of ordinary cement for the road base layer, which improves the utilization rate of phosphogypsum, reduces the cost of road construction, and improves the strength and water stability of the base layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638356A_ABST
    Figure CN119638356A_ABST
Patent Text Reader

Abstract

The high-content ardealite-cement stabilized macadam mixture provided by the embodiment of the invention comprises the following raw material components in parts by weight: 100-120 parts of graded macadam, 60-80 parts of ardealite, 5-10 parts of cement, 1-3 parts of a curing agent and 5-15 parts of water, cement and a curing agent are used for exciting the activity of original phosphogypsum, water is matched for stabilizing gravel, the strength and performance of the cement-phosphogypsum stabilized gravel base can be greatly improved by doping a small amount of the curing agent, and the problem that the engineering performance of phosphogypsum is poor is solved. The high-doping-amount phosphogypsum-cement is prepared in a manner of realizing high doping amount of the phosphogypsum to replace ordinary cement for a roadbed layer, so that the utilization rate of the phosphogypsum can be increased, the problem of phosphogypsum stockpiling can be relieved, and the construction cost of a road can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a crushed stone base material, in particular to a high-dosage phosphogypsum-cement stabilized crushed stone mixture and a preparation method thereof. Background Art

[0002] Phosphogypsum is a byproduct of phosphoric acid industrial production. The amount of stockpiling increases year by year, posing a huge threat to the environment and agricultural safety. In addition to gypsum, its main components also contain a small amount of impurities such as phosphorus, fluorine, organic matter, and heavy metal ions. Phosphogypsum is in the form of dispersed fine particles, with a free water content of 20% to 25%, a pH value of 2 to 4, and is acidic. The accumulation of phosphogypsum is serious across the country, and the yard is almost saturated. The phosphorus, fluorine and heavy metal pollutants remaining in the phosphogypsum will enter the ground and rivers with rainwater if not properly disposed, causing serious environmental hazards. At present, phosphogypsum is used as a cement retarder or to prepare gypsum products to improve the comprehensive utilization rate of phosphogypsum resources. The existing technology also uses phosphogypsum as a road material, but most of them are limited to using phosphogypsum as an auxiliary material, with a low mixing ratio, and a small amount of phosphogypsum consumed. In addition, due to the poor water stability of phosphogypsum and the presence of residual pollutants, it cannot be used directly and needs to be pretreated. Generally, the neutralization modification method is used to pre-treat the original phosphogypsum to form modified phosphogypsum, which eliminates the retarding factors (water-soluble phosphorus, water-soluble fluorine and residual flocculants) in the phosphogypsum. This makes the construction inconvenient and increases the construction cost.

[0003] Therefore, it is necessary to solve the technical problems of low mixing ratio, poor stability and water stability when phosphogypsum is used as pavement materials. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a high-dosage phosphogypsum-cement stabilized gravel mixture and a preparation method thereof, using cement and a curing agent to stimulate the activity of the original phosphogypsum, and adding water to stabilize the gravel, and increasing the dosage of phosphogypsum to achieve a high-dosage phosphogypsum-cement mixture to replace ordinary cement for road base.

[0005] The high-dosage phosphogypsum-cement stabilized crushed stone mixture of the present invention comprises the following components by weight: 100-120 parts of graded crushed stone, 60-80 parts of phosphogypsum, 5-10 parts of cement, 1-3 parts of curing agent, and 5-15 parts of water;

[0006] Further, the curing agent is a mixture of slag, silica fume and water glass;

[0007] Further, by weight, 1-3 parts of slag, 0.1-0.5 parts of silica fume, and 0.01-0.05 parts of water glass;

[0008] Further, the curing agent is a mixture of slag, silica fume, metakaolin and water glass;

[0009] Further, by weight, 1-3 parts of slag, 0.01-0.1 parts of silica fume, 0.1-0.5 parts of metakaolin, and 0.01-0.05 parts of water glass;

[0010] Further, the raw materials include the following components by weight: 110 parts of graded crushed stone, 70 parts of phosphogypsum, 7 parts of cement, 2 parts of curing agent, and 10 parts of water;

[0011] Further, the modulus of the water glass is 1-1.3;

[0012] Further, the modulus of the water glass is 1.2;

[0013] Furthermore, the phosphogypsum is raw phosphogypsum without pretreatment, and the phosphogypsum is dried and ground into particles with a particle size of less than 1 mm.

[0014] The invention discloses a method for preparing a high-dosage phosphogypsum-cement stabilized crushed stone mixture, comprising the following steps: directly and evenly mixing crushed stones of different gradations, phosphogypsum, cement, a curing agent and water.

[0015] The beneficial effects of the present invention are: a high-dosage phosphogypsum-cement stabilized gravel mixture and a preparation method thereof, wherein cement and a curing agent are used to stimulate the activity of the original phosphogypsum, and water is added to stabilize the gravel, and a small amount of curing agent can be added to greatly improve the strength and performance of the cement-phosphogypsum stabilized gravel base layer, thereby solving the problem of poor engineering performance of phosphogypsum, and realizing the preparation of high-dosage phosphogypsum-cement in a high-dosage manner to replace ordinary cement for road base layer, which can not only improve the utilization rate of phosphogypsum and alleviate the problem of phosphogypsum storage, but also reduce the construction cost of roads. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:

[0017] Figure 1 is the SEM image of the specimen of Example 1;

[0018] Figure 2 is the SEM image of the specimen of Example 2;

[0019] Figure 3 Figure 2 is the process diagram of the unconfined compressive strength test.

[0020] Figure 4 It is the unconfined compressive strength of high-content phosphogypsum stabilized material;

[0021] Figure 5 This is the water stability result of high-dosage phosphogypsum stabilized material;

[0022] Figure 6 These are the SEM-EDS test results of high-dosage phosphogypsum stabilized materials. DETAILED DESCRIPTION

[0023] The high-dosage phosphogypsum-cement stabilized gravel mixture of the present embodiment comprises the following components by weight: 100-120 parts of graded gravel, 60-80 parts of phosphogypsum, 5-10 parts of cement, 1-3 parts of curing agent, and 5-15 parts of water. The phosphogypsum does not need to be pretreated, and the activity of the original phosphogypsum is directly stimulated by cement and curing agent, and the gravel is stabilized by water. The addition of a small amount of curing agent can greatly improve the strength and performance of the cement-phosphogypsum stabilized gravel base, solve the technical problem of poor engineering performance of phosphogypsum, and realize the preparation of high-dosage phosphogypsum-cement in a high-dosage manner to replace ordinary cement for road base.

[0024] In this embodiment, a binary curing agent is used, and the curing agent is a mixture of slag, silica fume and water glass; by weight, 1-3 parts of slag, 0.1-0.5 parts of silica fume, and 0.01-0.05 parts of water glass; or a ternary curing agent is used, and the curing agent is a mixture of slag, silica fume, metakaolin and water glass; by weight, 1-3 parts of slag, 0.01-0.1 parts of silica fume, 0.1-0.5 parts of metakaolin, and 0.01-0.05 parts of water glass; under the action of sodium alkali as water glass in the curing agent, the basic unit structure of Al2O3 disintegrates and reacts with Ca 2+ Combined, at the same time, a water molecule and an oxygen atom of SO3 and Ca 2+ Combined, the two are Ca 2+ The center combines to form a skeleton, and in the process of continuous combination of the skeleton, ettringite is gradually formed. On the other hand, the silicon-oxygen tetrahedral structure and water molecules are combined with Ca 2+ Combined to form C-(A)-SH gel, while Ca 2+ The ettringite skeleton and gypsum as the center are connected and adhered to the C-(A)-SH gel, thus forming a dense structure that gives the system a certain strength.

[0025] The preferred embodiment is that the raw materials include the following components by weight: 110 parts of graded crushed stone, 70 parts of phosphogypsum, 7 parts of cement, 2 parts of curing agent (slag, silica fume, water glass), and 10 parts of water. Or 100 parts of graded crushed stone, 60 parts of phosphogypsum, 5 parts of cement, 1 part of curing agent ((slag, silica fume, water glass), and 5 parts of water; 120 parts of graded crushed stone, 80 parts of phosphogypsum, 10 parts of cement, 3 parts of curing agent (slag, silica fume, metakaolin, water glass), and 15 parts of water; 100 parts of graded crushed stone, 80 parts of phosphogypsum, 5 parts of cement, 3 parts of curing agent (slag, silica fume, metakaolin, water glass), and 5 parts of water; 115 parts of graded crushed stone, 70 parts of phosphogypsum, 8 parts of cement, 2 parts of curing agent (slag, silica fume, metakaolin, water glass), and 10 parts of water;

[0026] A more preferred embodiment is 108 parts of graded crushed stone, 63 parts of phosphogypsum, 7 parts of cement, a binary curing agent (2 parts of slag, 0.2 parts of silica fume, 0.04 parts of water glass), and 10 parts of water; or, 108 parts of graded crushed stone, 63 parts of phosphogypsum, 7 parts of cement, a ternary curing agent (2 parts of slag, 0.06 parts of silica fume, 0.14 parts of metakaolin, 0.04 parts of water glass), 10 parts of water, and so on.

[0027] In this embodiment, the modulus of the water glass is 1-1.3; preferably, the modulus of the water glass is 1.2. The modulus of the water glass affects the construction performance, flexural resistance and compressive resistance of the slurry. Generally, the higher the modulus of the water glass, the greater the viscosity and the higher the adhesion. The water glass with a lower modulus used in the present invention can meet both the construction requirements and the flexural resistance and compressive strength requirements.

[0028] In this embodiment, the phosphogypsum is raw phosphogypsum without pretreatment, and the phosphogypsum is dried and then ground into particles with a particle size of less than 1 mm.

[0029] The present embodiment also discloses a method for preparing a high-dosage phosphogypsum-cement stabilized crushed stone mixture, comprising the following steps: directly mixing graded crushed stone, phosphogypsum, cement, curing agent and water. When a binary curing agent (a mixture of slag, silica fume and water glass) is used, the graded crushed stone, phosphogypsum, cement, slag and silica fume are mixed, then water glass solution and water are added to mix evenly, and the mixture is spread and compacted during on-site construction; when a ternary curing agent is used, the graded crushed stone, phosphogypsum, cement, slag, metakaolin and silica fume are mixed, then water glass solution and water are added to mix evenly, and the mixture is spread and compacted during on-site construction.

[0030] Embodiment 1

[0031] The high-dosage phosphogypsum-cement stabilized gravel mixture of this embodiment comprises, by weight, 108 parts of graded gravel, 63 parts of phosphogypsum, 7 parts of cement, a binary curing agent (2 parts of slag, 0.2 parts of silica fume, 0.04 parts of water glass), and 10 parts of water.

[0032] In order to test the performance of high-dosage phosphogypsum-cement stabilized gravel mixture, the mixture was made into specimens for relevant performance tests.

[0033] The specimen preparation method is as follows: S1, the phosphogypsum retrieved from the phosphogypsum storage site is dried at 105°C to constant weight, and then ground into fine particles less than 1 mm by a ball mill.

[0034] S2, mix crushed stone, phosphogypsum, cement, slag and silica fume of different grades and spread them evenly in a rectangular dish, spray the water and water glass solution calculated in advance on the sample evenly, use a small shovel to fully mix the sample until it is uniform, and then put it into a sealed container or plastic bag to soak for 8 hours;

[0035] S3, put the binder into a mold with an inner diameter of 150mm and a wall thickness of 10mm, which should be high enough to allow 150mm to remain after the upper and lower pads are placed. Put the lower pad that matches the test mold into the lower part of the test mold, but expose about 20mm. Pour the same mass of mixed material into the test mold in 2 to 3 times, and use a tamping rod to gently and evenly compact it after each pouring; put the entire test mold (together with the upper and lower pads) on a jack or press in the reaction frame and pressurize it at a loading rate of 1mm / min until the upper and lower pressure columns are pressed into the test mold, and maintain the pressure for 2min; demould after curing for 4 hours under natural curing conditions; weigh the mass m of the test piece, and the test piece should be accurate to 0.1g; then measure the height h of the test piece with a vernier caliper, accurate to 0.1mm, check the height and mass of the test piece, and the test piece that does not meet the molding standard shall be regarded as waste. After weighing, the test piece shall be immediately sealed in a plastic bag, covered with a damp towel, and moved to the breeder's room.

[0036] Take out the specimen that has been immersed in water for 24 hours from the water, absorb the moisture on the surface of the specimen with a soft cloth, and weigh the mass of the specimen.

[0037] Place the specimen on a pavement material strength tester or press, and place a flat ball seat on the lifting platform for a compression test. During the test, the loading rate should be maintained at 1mm / min. The 7d unconfined compressive strength of the specimen is recorded as 6.01MPa, which meets the unconfined compressive strength requirements (5-7MPa) for extremely heavy and extra-heavy traffic bases on expressways and first-class highways.

[0038] The specimens with an age of 7 days were selected for microscopic SEM analysis. Figure 1 As shown in the figure, a large number of needle-shaped calcium sulfonate crystals and foil-like CSH gels that are tightly bonded or cover the interface transition zone can be observed. There is also a flocculent calcium aluminosilicate hydrate (C-(A)-SH) gel formed by the hydration of the curing agent. This is because the alkaline slag-based polymer curing agent neutralizes the weakly acidic environment provided by the high-dosage phosphogypsum to a certain extent, stimulating the hydration activity of cement. At the same time, the large amount of Ca provided by the phosphogypsum 2+ Under the action of the alkali activator, a volcanic ash reaction occurs with SiO2 and Al2O3 in slag and silica fume, and CSH gel and C-(A)-SH gel are generated through a secondary hydration reaction different from cement hydration. The two hydrated gels together wrap the aggregate interface area more tightly and fix the ettringite crystal skeleton by bonding, making the internal pores smaller, the overall structure denser and the strength higher.

[0039] The 7-day-old specimens of Example 1 and the original phosphogypsum were selected for leaching toxicity test, as shown in Table 1. Table 1 shows that the PO4 3- The leaching concentration is 315.923 mg / L, while the PO4 3- The leaching concentration was 0.196 mg / L, which was reduced by about 99%. The test pieces in Example 1 all met the first-level standard of GB 8978-1996 "Sewage Discharge Standard" and GB 5085.3-2007 "Hazardous Waste Identification Standard Leaching Toxicity Identification" for F - and PO4 3- The main heavy metals in the original phosphogypsum are As 3+ The leaching concentration is 1.628 mg / L, which exceeds the standard value of 0.5 mg / L in the first-level standard of GB 8978-1996. 3+ The leaching concentration was reduced by about 99.5%, and the leaching concentrations of other heavy metals were all lower than the limit values ​​in the relevant standards.

[0040] Table 1 Example 1 Test piece and original phosphogypsum leaching toxicity

[0041]

[0042] Embodiment 2

[0043] The high-dosage phosphogypsum-cement stabilized gravel mixture of this embodiment comprises, by weight, 108 parts of graded gravel, 63 parts of phosphogypsum, 7 parts of cement, a ternary curing agent (2 parts of slag, 0.06 parts of silica fume, 0.14 parts of metakaolin, 0.04 parts of water glass), and 10 parts of water.

[0044] In order to test the performance of high-dosage phosphogypsum-cement stabilized gravel mixture, the mixture was made into specimens for relevant performance tests.

[0045] The specimen preparation method is as follows: S1, phosphogypsum retrieved from the phosphogypsum storage site was dried at 105 °C to constant weight and ground into fine particles less than 3 mm by a ball mill;

[0046] S2, mix crushed stone, phosphogypsum, cement, slag and silica fume of different grades and spread them evenly in a rectangular dish, spray the water and water glass solution calculated in advance on the sample evenly, use a small shovel to fully mix the sample until it is uniform, and then put it into a sealed container or plastic bag and soak it for 8 hours;

[0047] S3, load the bonding material into a mold with an inner diameter of 150mm and a wall thickness of 10mm. The height should be enough to allow 150mm of space left after the upper and lower pads are placed. The preparation method is the same as the steps in Example 1S4.

[0048] Place the specimen on a pavement material strength tester or press, and place a flat ball seat on the lifting platform for a compression test. During the test, the loading rate should be maintained at 1mm / min, and the 7d unconfined compressive strength of the specimen is recorded as 6.6MPa, which meets the unconfined compressive strength requirements (5-7MPa) for extremely heavy and extra-heavy traffic bases of expressways and first-class highways.

[0049] The 7-day-old specimen of Example 2 was selected for microscopic SEM analysis. Figure 2 As shown, it can be observed that compared with the specimen of Example 1, the specimen of Example 2 generates more needle-rod-shaped calcium sulfonate crystals and flocculent hydrated calcium aluminosilicate gel, and the transition interface between the cementitious material and the aggregate is more compact. This is because the addition of metakaolin in Example 2 can provide more active SiO2 and Al2O3, which can promote the rehydration of cement and combine with phosphogypsum to generate more calcium sulfonate, thereby further improving the strength.

[0050] The 7-day-old specimen of Example 2 and the original phosphogypsum were selected for leaching toxicity test, as shown in Table 1. Table 2 shows that the leaching of PO43-, F-, As 3+ They are 5.434mg / L, 0.085mg / L and 0.023mg / L respectively, which are far lower than the first-level standard of GB8978-1996 "Sewage Discharge Standard" and GB 5085.3-2007 "Hazardous Waste Identification Standard Leaching Toxicity Identification" for F - PO4 3- and As 3+ The leaching toxicity concentration requirements of the heavy metals are met. And the leaching concentrations of other heavy metals are all lower than the limit values ​​in the relevant standards.

[0051] Table 2 Example 2 test specimen and original phosphogypsum leaching toxicity

[0052]

[0053] Embodiment 3

[0054] 1. Unconfined compressive strength test analysis:

[0055] Referring to the T0805-1994 test method in JTG E51-2009 "Test Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering", 100mm×100mm cylindrical specimens were formed, placed in plastic bags and cured in a standard curing room. The specimens were taken out at 7d, 28d, and 60d curing age and cured for 24h to conduct unconfined compressive strength tests. The test process is as follows: Figure 3 The results are as follows Figure 4 As shown:

[0056] From the overall point of view, when the cement: phosphogypsum ratio is the same, as the proportion of the two in the stabilized material increases, the compressive strength of the specimen shows a trend of first increasing and then decreasing; and the larger the cement-phosphogypsum ratio, the higher the compressive strength of the specimen. From Figures (a), (b), and (c), it can be seen that the effect is better when the cement-phosphogypsum ratio is 40%. In engineering applications, the recommended cement dosage is generally not more than 5%, so A8, that is, 5% cement + 35% phosphogypsum + 60% graded crushed stone, is selected as the optimal mix ratio. Its 7d, 28d, and 60d unconfined compressive strengths are 3.7MPa, 5.2MPa, and 6.5MPa, respectively. The 7d strength can meet the strength requirements of the base of expressways and first-class highways under medium and light traffic. After using two curing agents (binary and ternary) for reinforcement, only using curing agents instead of 1% of cement, the 7d strength of the high-dosage phosphogypsum-cement-curing agent stabilized material has been increased by about 50%, and both meet the strength requirements of the base of expressways and first-class highways under extremely heavy and extra-heavy traffic. As the curing age increases, the strength increase can be further improved. The unconfined compressive strength of B1 (1% binary curing agent + 4% cement + 35% phosphogypsum + 60% graded crushed stone) at 7d, 28d and 60d is 6MPa, 9MPa and 10.7MPa respectively, and the unconfined compressive strength of B6 (1% ternary curing agent + 4% cement + 35% phosphogypsum + 60% graded crushed stone) at 7d, 28d and 60d is 6.6MPa, 9.3MPa and 11.3MPa respectively. The lateral comparison of the unconfined compressive strength of the products at 7d is shown in Table 3.

[0057] Table 3 Transverse comparison of 7d unconfined compressive strength of products

[0058]

[0059] The 7d-age unconfined compressive strength standards of cement stabilized materials are shown in the following table:

[0060] 7d age unconfined compressive strength standard R of cement stabilized materials d (MPa)

[0061]

[0062] Note: 1. When the highway grade is high, the traffic load grade is high, or the structural safety requirement is high, it is recommended to adopt the upper limit strength standard.

[0063] 2. The strength standards in the table refer to the representative values ​​of unconfined compressive strength at 7 days of age. The same applies to the following tables in this section.

[0064] 2. Water stability test

[0065] In order to study the water stability of high-content phosphogypsum-cement stabilized gravel base, the specimens were formed according to the test method T 0805-1994 in JTG E51-2009 "Test Code for Stabilized Materials of Inorganic Binders for Highway Engineering" and standard cured for 48 hours. The specimens were taken out of the plastic bag for immersion curing. After curing for 7 days and 28 days, the unconfined compressive strength in the saturated state was tested, and the ratio of the unconfined compressive strength in the saturated state to the unconfined compressive strength under standard curing was used as its water stability coefficient. The results are shown in Figure 2. Figure 5 shown.

[0066] As can be seen from the figure, the water stability coefficient of the optimal mix A8 of high-dosage phosphogypsum-cement stabilized material is good, among which the 7d strength ratio can reach 76.4%, and 28d can reach 78.8%; after adding the curing agent, the water stability coefficient can be further improved, among which the 7d strength ratio of B1 reaches 79%, and 28d can reach 86.9%, and the 7d strength ratio of B6 reaches 78.8%, and 28d can reach 92.4%. From the perspective of water stability, the effects of the ternary curing agent and the binary curing agent are similar at the 7d curing age, but with the increase of curing time, a more stable structure with fewer pores is formed inside the stabilized material with the addition of the ternary curing agent, which makes the specimen better in water resistance.

[0067] 3. SEM-EDS microscopic analysis

[0068] Figure 6The SEM-EDS images of the interface transition zone of the phosphogypsum-cement stabilized material and the phosphogypsum-cement-curing agent stabilized material samples of the above-mentioned embodiment at 28 days. Hydration products are generated in the interface zone inside the phosphogypsum-cement stabilized material, mainly clustered and foil-shaped calcium aluminate hydrate (CSH) gel, plate-like rhombus-shaped or short-column-shaped gypsum crystals, needle-shaped calcium sulfonate (AFt) crystals, and flaky Ca(OH)2 crystals. In Figure (a), the amount of hydration products generated is small, the density of the connection between the aggregate and the hydration products in the interface zone is low, and there are large pores. This is because the high amount of phosphogypsum provides a weakly acidic environment, which makes the hydration progress of cement particles slow in the initial stage of the reaction, and the cement particles will quickly generate dense AFt on the surface in a sulfate-rich environment, which hinders the further hydration of the cement particles. After 28 days of curing, there is still only a small amount of clustered CSH gel inside the material, which is not enough to fill the pores between the aggregate and the phosphogypsum particles, resulting in a loose overall structure. In Figure (b), it can be observed that with the increase of cement content, the number of foil-like CSH gel and needle-like AFt in the interface area increases significantly, and a large amount of AFt is interspersed in the CSH gel to form a skeleton, indicating that the cement hydration effect is good. In Figure (c), AFt is tightly staggered and overlapped, filling the pores between aggregates well, and a large amount of CSH gel further improves the strength through bonding. In Figures (d) and (e), not only a large number of needle-like AFt and foil-like CSH gels can be observed, but also some flocculent hydrated calcium aluminosilicate (C-(A)-SH) gels are present. This is formed by the reaction of slag-based polymer curing agent. The alkaline curing agent neutralizes the weakly acidic environment of phosphogypsum and stimulates the hydration of cement. The two hydrated gels generated by the reaction wrap the aggregate interface area more tightly, with fewer pores, and AFt interspersed in it makes the overall structure more compact.

[0069] from Figure 5 It can be seen from the EDS in that the main elements of the hydrated gel are Ca, Si, O, Al, etc. Combined with XRD and SEM, this shows that the tested hydration products are mainly CSH and AFt. The O content in EDS point 1 is high, and the Ca and Si contents are low, which indicates that there are fewer cement hydration products in the material, and there are still more CaSO4 that have not participated in the reaction. The Ca, Si, and Al content in EDS points 2 and 3 has increased to a certain extent, indicating that with the increase of cement content, the CSH and AFt contents have been increased, and this phenomenon has also been observed in SEM. The Ca and Si contents in EDS points 4 and 5 are high, indicating that more CSH and C-(A)-SH are generated. No P element was detected in the five EDS points, indicating that the phosphorus impurities in the phosphogypsum are adsorbed by CSH and solidified inside the gel lattice. There is a small amount of F element in EDS, which indicates that the filling and encapsulation of the hydrated gel can fix the fluoride in the phosphogypsum, and only a small amount of fluorine-containing pollutants escape from the gel surface.

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A high-dosage phosphogypsum-cement stabilized gravel mixture, characterized in that: The raw materials include the following components by weight: 100-120 parts of graded crushed stone, 60-80 parts of phosphogypsum, 5-10 parts of cement, 1-3 parts of curing agent, and 5-15 parts of water.

2. The high-dosage phosphogypsum-cement stabilized gravel mixture according to claim 1, characterized in that: The curing agent is a mixture of slag, silica fume and water glass.

3. The high-dosage phosphogypsum-cement stabilized gravel mixture according to claim 2, characterized in that: By weight, 1-3 parts of slag, 0.1-0.5 parts of silica fume, and 0.01-0.05 parts of water glass.

4. The high-dosage phosphogypsum-cement stabilized gravel mixture according to claim 1, characterized in that: The curing agent is a mixture of slag, silica fume, metakaolin and water glass.

5. The high-dosage phosphogypsum-cement stabilized gravel mixture according to claim 4, characterized in that: In parts by weight, 1-3 parts of slag, 0.01-0.1 parts of silica fume, 0.1-0.5 parts of metakaolin, and 0.01-0.05 parts of water glass.

6. The high-dosage phosphogypsum-cement stabilized gravel mixture according to claim 1, characterized in that: The raw materials include the following components by weight: 110 parts of graded crushed stone, 70 parts of phosphogypsum, 7 parts of cement, 2 parts of curing agent, and 10 parts of water.

7. The high-dosage phosphogypsum-cement stabilized gravel mixture according to claim 1, characterized in that: The modulus of the water glass is 1-1.

3.

8. The high-dosage phosphogypsum-cement stabilized gravel mixture according to claim 7, characterized in that: The modulus of the water glass is 1.

2.

9. The high-dosage phosphogypsum-cement stabilized gravel mixture according to claim 1, characterized in that: The phosphogypsum is raw phosphogypsum without pretreatment, and the phosphogypsum is dried and then ground into particles with a particle size of less than 1 mm.

10. The method for preparing a high-dosage phosphogypsum-cement stabilized gravel mixture according to any one of claims 1 to 9, characterized in that: The following steps are involved: Directly mix the graded crushed stone, phosphogypsum, cement, curing agent and water evenly.

Citation Information

Cited By

  • High-content phosphogypsum pavement base material and preparation method thereof

    CN120794554A

  • High-content phosphogypsum pavement base material and preparation method thereof

    CN120794554B